ASPERGILLUS SP. PADA ULKUS KORNEA - Hesty Rhauda Ashan; Ellyza Nasrul; Abdul Aziz Djamal (Universitas Fort De Kock, 2020)
Aspergillosis is a disease caused by Aspergillus sp., especially Aspergillus fumigatus which induce granulomatosis inflammation in mucous membranes, eyes, bronchi, ears. Aspergillus sp. microscopically characterized as septate and branched hyphae. Fungal corneal ulcers are more common in tropical climates. Aspergillus sp. is the most common fungi causes corneal ulcer. Risk factors include the use of antibiotics, long-term corticosteroids, trauma, contact lenses, and corneal surgery. 50-year-old female with main complaint: increased redness and pain of the right eye after trauma from twig. Palpebral edema, conjunctival injection, ciliary injection, corneal ulcers, maceration, and impending were found from physical examination of the right eye. Fungal culture on sabouraud dextrose agar (SDA) culture media found growth of fungi Aspergillus sp. which macroscopically has fertile hyphae on the surface and vegetative hyphae below the surface, and microscopically characterized as septate and branching hyphae. Corneal ulcers in the tropics are mostly caused by fungi. Aspergillus sp. and Fusarium sp. is most commonly found in tropical climates, while Candida is more commonly found in cold climates. Diagnosis of corneal ulcer ec Aspergillus sp. is obtained based on history, clinical manifestation and found Aspergillus sp. from fungal culture.